Nav1.8 neurons are involved in limiting acute phase responses to dietary fat - Swalpa Udit; Michael Burton; Joseph M. Rutkowski; Syann Lee; Angie L. Bookout; Philipp E. Scherer; Joel K. Elmquist; Laurent Gautron (Elsevier, 2017)
Objective and methods: Metabolic viscera and their vasculature are richly innervated by peripheral sensory neurons. Here, we examined the metabolic and inflammatory profiles of mice with selective ablation of all Nav1.8-expressing primary afferent neurons. Results: While mice lacking sensory neurons displayed no differences in body weight, food intake, energy expenditure, or body composition compared to controls on chow diet, ablated mice developed an exaggerated inflammatory response to high-fat feeding characterized by bouts of weight loss, splenomegaly, elevated circulating interleukin-6 and hepatic serum amyloid A expression. This phenotype appeared to be directly mediated by the ingestion of saturated lipids. Conclusions: These data demonstrate that the Nav1.8-expressing afferent neurons are not essential for energy balance but are required for limiting the acute phase response caused by an obesogenic diet.